A design methodology to reduce the embodied carbon of concrete buildings using thin-shell floors. (15th March 2020) - Hawkins, Will; Orr, John; Ibell, Tim; Shepherd, Paul
Graphical abstract: Highlights: This paper considers novel vaulted floors with textile reinforced concrete shells. A practical, repeatable and conservative design methodology is described. Long-term deflections are small and do not govern the overall design. Embodied carbon is reduced by 53–58% compared to an equivalent flat slab. Thin-shell floors are a practical way of reducing the embodied carbon of buildings. Abstract: This paper explores the potential of thin concrete shells as low-carbon alternatives to floor slabs and beams, which typically make up the majority of structural material in multi-storey buildings. A simple and practical system is proposed, featuring pre-cast textile reinforced concrete shells with a network of prestressed steel tension ties. A non-structural fill is included to provide a level top surface. Building on previous experimental and theoretical work, a complete design methodology is presented. This is then used to explore the structural behaviour of the proposed system, refine its design, and evaluate potential carbon savings. Compared to flat slabs of equivalent structural performance, significant embodied carbon reductions (53–58%) are demonstrated across spans of 6–18 m. Self-weight reductions of 43–53% are also achieved, which would save additional material in columns and foundations. The simplicity of the proposed structure, and conservatism of the design methodology, indicate that further savings could be made with future refinements. These results show that considerable embodied carbon reductions are possible through innovative structural design, and that thin-shell floors are a practical means of achieving this.